ELECTRIC CURRENT MONITORING SYSTEM USING A MICROCONTROLLER AND IOT MODULE - Nurrohmat, Alif Fakhri; Sopian, Dicky Muhamad; Pradipta, Kristoforus Iubileagung Hanang; Suci, Putra Hari; Luthfiana, Wildan; Wahyu, Ari P (CENTRAL ASIA AND THE CAUCASUS, 2022)
Electricity is clearly needed by all people from various walks of life. The electrical system is developing rapidly today, starting with a centralized system, the distribution process and ending with consumers as users of electrical resources. As electricity consumers, we don't know how much electricity we use every day, especially when it comes to the electronic devices we use every day. In addition, in recent years there have been frequent internal accidents caused by power outage or short circuit and excess electrical capacitance, which can cause all electricity to be cut off. These problems can actually be solved by power quality (capacity) monitoring systems and power distribution management. This system is a system that helps consumers to monitor the power consumption of household electrical appliances. The purpose of this research is to create a power monitoring system for several electronic devices used at home and the output power consumed can be viewed through the Thingspeak website. This system consists of a microcontroller that uses an ACS712 flow sensor to detect power, uses an ESP8266 module to transmit data to Thingspeak Web, an Arduino module to collect data and run the system, and an LCD to view power consumption results.